Small mammal distributional patterns in northwestern Argentina - Sandoval Salinas, Maria Leonor (2015)
Quantitative evaluations of species distributional congruence allow evaluating previously proposed biogeographic regionalization and even identify undetected areas of endemism. The geographic scenery of Northwestern Argentina offers ideal conditions for the study of distributional patterns of species since the boundaries of a diverse group of biomes converge in a relatively small region, which also includes a diverse fauna of mammals. In this paper we applied a grid-based explicit method in order to recognize Patterns of Distributional Congruence (PDCs) and Areas of Endemism (AEs), and the species (native but non-endemic and endemic, respectively) that determine them. Also, we relate these distributional patterns to traditional biogeographic divisions of the study region and with a very recent phytogeographic study and we reconsider what previously rejected as ‘spurious’ areas. Finally, we assessed the generality of the patterns found. The analysis resulted in 165 consensus areas, characterized by seven species of marsupials, 28 species of bats, and 63 species of rodents, which represents a large percentage of the total species (10, 41, and 73, respectively). Twenty-five percent of the species that characterize consensus areas are endemic to the study region and define six AEs in strict sense while 12 PDCs are mainly defined by widely distributed species. While detailed quantitative analyses of plant species distribution data made by other authors does not result in units that correspond to Cabrera’s phytogeographic divisions at this spatial scale, analyses of animal species distribution data does. We were able to identify previously unknown meaningful faunal patterns and more accurately define those already identified. We identify PDCs and AEs that conform Eastern Andean Slopes Patterns, Western High Andes Patterns, and Merged Eastern and Western Andean Slopes Patterns, some of which are re-interpreted at the light of known patterns of the endemic vascular flora. Endemism do not declines towards the south, but do declines towards the west of the study region. Peaks of endemism are found in the eastern Andean slopes in Jujuy and Tucumán/ Catamarca, and in the western Andean biomes in Tucumán/Catamarca. The principal habitat types for endemic small mammal species are the eastern humid Andean slopes. Notwithstanding, arid/semi-arid biomes and humid landscapes are represented by the same number of AEs. Rodent species define 15 of the 18 General Patterns, and only in one they have no participation at all. Clearly, at this spatial scale, non-flying mammals, particularly rodents, are biogeographically more valuable species than flying mammals (bat species).